'Ah, but I was so much older then, I'm younger than that now': Cancer and a Virtual Relationship. Issue 1 (2nd January 2016) - Kiernan, Hugh
ABSTRACT: Responses of young people to cancer often include understandable references to 'having my life taken away'. A correlation between illness and loss of opportunity, birth right, dreams and plans shows in expressive writing, blogging and forum discussions by young people. Skilled young writers, poets and artists have paid attention to the theme of life being derailed by a cancer diagnosis. Jess Mason was diagnosed with leukaemia in her early twenties. She also suffered from several consequential conditions. I got to know her through her poetry. I was a fellow cancer sufferer. In addition to loss, her poetry themes include speaking back to the medical impositions, the social expectations and the relationship issues that arose because of her illness. Her poetry is distinctive, assured and challenging. It includes sophisticated phrasing, arresting imagery and tonal qualities that underline her themes. Jess' death, four years after we first met in an online expressive writing group, led me to contact her family and explore how we might bring her poems to the attention of a wider audience. A selection of Jess' poems are included and commented on here.